Product Development and Marketing Quality Improvement Training for Craftswomen of Purun Woven: Pelatihan Pengembangan Produk dan Peningkatan Kualitas Pemasaran bagi Pengrajin Anyaman Purun - Susanti, Dewi Sri; Annisa, Selvi; Rahkmawati, Yeni; Adzim, Muhammad Fauzan; Genardi, Angelina Ivanna; Oktaviani, Viona (Universitas Lancang Kuning, 2024)
One of the villages in Banjarbaru has a unique handicraft product because it is made from Purun plants, a type of shrub that grows wild in swamp areas. The products made by the community around Palam Village are bags and accessories woven from Purun rat plant materials. So far, the handicraft is enough to provide additional income for housewives but has not provided optimal results because it has yet to implement a digital marketing strategy. The bag products produced are also relatively simple and have yet to be modified to gain more value in sales. This community service project aimed to train housewives in product development so they could produce Purun bag items more skillfully. Furthermore, instruction was provided on creating poster designs using the Canva software as a digital marketing tool. During the training, the artisans had the chance to try creating Purun bags by hand and creating advertising posters using their phones. The end training outcomes demonstrated that the artisans could incorporate the instruction into their creations. The assessment form revealed that the artisans were highly motivated to participate in the training and expressed hopes that conducting more of this kind of instruction in the future would be possible.